On The History of The Emergence of The National Press In The Bukhara Emirate - Kamol Ishanqulovich Hazratkulov (Euro Asian Journal Publishing, 2023)
The article analyzes the journalistic materials on various topics covering the ideas of enlightenment published in the newspaper "Bukharoisharif" of the Bukhara Jadids, which operated at the beginning of the last century, and gives an assessment of the historical processes of that time. The newspaper materials were interpreted by the author based on the factual method, historical processes were studied and the important aspects of the modernist movement were revealed.
Keywords: nation; nationpress